Analysis Of Use Of Telemedicine Services During Pandemic In Rsia Stella Maris Medan - Said Munazar Rahmat; Ermi Girsang; Maya Sari Mutia; Ali Napiah Nasution (International Journal of Health and Pharmaceutical (IJHP), 2022)
Covid-19 is an infectious disease that will become a global pandemic in 2020. To reduce the transmission rate, WHO has issued various recommendations for the community, such as the use of masks, regular hand washing, coughing and sneezing etiquette, keeping a distance between people, avoiding crowded places, and others. The existence of public restrictions creates new problems for patients because of difficulties in seeking treatment. Telemedicine is a form of telehealth, which is a health service that is carried out remotely. This technology makes it easier for patients to interact with doctors without having to meet face to face. The purpose of this study was to determine the level of satisfaction of users of telemedicine services at RSIA Stella Maris Medan. The type of research used is non-experimental quantitative with a quantitative analytical study design. The population and samples used were 186 users of telemedicine services at RSIA Stella Maris. The results showed that users considered the features of the availability of options to be able to choose the treating doctor, the confidentiality of medical records, the stability of the internet network, the friendly and ready to help the attitude of the nurses, and the long waiting time for the drug delivery process as the most important features of each service dimension. To improve the quality of RSIA Stella Maris telemedicine services, many features are a priority to be improved, as well as features are maintained.